Analysis Of The Influence Of Product Quality And Price Perception On Purchase Decision Of Mm Coffee In Surabaya - Fahrezy, Moch Rizky; Soebiantoro, Ugy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The growth of the coffee beverage industry in Surabaya has shown a significant increase, prompting local businesses such as MM Coffee to better understand the factors that influence consumer purchasing decisions, especially in light of declining product sales between 2020 and 2023. This study aims to analyze the influence of product quality and price perception on consumers' purchasing decisions at MM Coffee. A quantitative approach was employed, using Partial Least Squares (PLS) based on Structural Equation Modeling (SEM), with data analysis conducted using SmartPLS 4.0 software. The study sample consisted of 91 respondents who are MM Coffee consumers in Surabaya, selected through purposive sampling. Data was collected via an online questionnaire. The results of the analysis show that product quality has a positive and significant effect on purchasing decisions. Similarly, price perception also has a positive and significant effect on purchasing decisions. These findings imply that MM Coffee must focus on improving product quality, including aspects such as taste and consistency, while maintaining a fair price perception that aligns with the value offered. Collectively, the two variables explain more than half of the variation in purchasing decisions. This emphasizes the importance of maintaining product quality and building a price perception that reflects the value perceived by consumers